The Effect of Discipline and Work Motivation on Employee Performance at PT Telkom Indonesia Tbk. Sto Ciputat, South Tangerang City - Muhammad Gandung; Suwanto Suwanto (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to see: (1) To see the discipline at PT Telkom Indonesia Tbk. Sto Ciputat Kota Tangerang Selatan, (2) To determine the work motivation of employees at PT Telkom Indonesia Tbk. Sto Ciputat Kota Tangerang Selatan, (3 To see the effect of attitude and motivation on the performance of employees of PT Telkom Indonesia Tbk. Sto Ciputat Kota Tangerang Selatan. This research is a survey research with a quantitative approach. The sample of this research is employees of PT Telkom Indonesia Tbk. Sto Ciputat Kota. South Tangerang, the sample of this study was determined as many as 65 employees or all employees of PT Telkom Indonesia Tbk. Sto Ciputat, South Tangerang City. Data analysis techniques used are descriptive analysis and inferential analysis, namely: (1) Validity and Reliability Test, (2) Classical Assumption Test, (3) Analysis of the Coefficient of Determination (r²), (4) Analysis of Correlation Coefficients, (5) Simple Linear Regression Analysis, (7) Multiple Linear Regression Analysis, (8) Analysis of Hypothesis Testing with Partial Test (t-test) and Simultaneous Test ( test f). Based on the results of this study prove that work motivation has a significant effect on employee performance by obtaining the results of the variable t-test work motivation bell by comparing t-count with t-table, t-count> t-table (5,228> 1,998) with a significance probability value of 0,000 <0.05.